Relationships of blood pressure and control with microvascular dysfunction in type 2 diabetes - Hayfron-Benjamin, Charles F.; Quartey-Papafio, Theresa Ruby; Amo-Nyarko, Tracy; Antwi, Ewuradwoa A; Vormatu, Patience; Agyei-Fedieley, Melody Kwatemah; Obeng, Kwaku Amponsah (Diabetes epidemiology and management, 2023)
•In West Africans with T2D, neuropathy was the commonest microvascular complication.•Hypertension was independently associated with neuropathy and nephropathy in T2D.•Increasing systolic BP was independently associated with nephropathy in T2D.•Increasing diastolic BP was independently associated with nephropathy in T2D.•Systolic/diastolic BP was not independently associated with neuropathy/retinopathy. In type 2 diabetes mellitus (T2D), cardiovascular risk factors including glycemic control differentially affect various microcirculatory beds. To date, studies comparing the impact of blood pressure (BP) on various microvascular beds in T2D are limited. We assessed the associations of BP and its control with neural, renal, and retinal microvascular dysfunction. This was a cross-sectional study among 403 adults with T2D. Microvascular dysfunction was based on nephropathy (albumin-creatinine ratio ≥ 30 mg/g), neuropathy (vibration perception threshold ≥ 25 V and/or Diabetic Neuropathy Symptom score > 1), and retinopathy (based on retinal photography). Logistic regression was used to examine the associations of hypertension, systolic BP, and diastolic BP with microvascular dysfunction with adjustments for age, sex, diabetes duration, smoking pack years, HbA1c concentration, total cholesterol concentration, and BMI. The mean age (± SD), proportion of females, and proportion of hypertensives were 56.35 (± 9.91) years, 75.7%, and 49.1%, respectively. In a fully adjusted model, hypertension was significantly associated with neuropathy [odds ratio 3.44, 95% confidence interval 1.96–6.04, P < 0.001] and nephropathy [2.05 (1.09–3.85), 0.026] but not for retinopathy [0.98 (0.42–2.31), 0.970]. Increasing Z-score systolic BP was significantly associated with nephropathy [1.43 (1.05–1.97), 0.025] but not for neuropathy [1.28 (0.98–1.67), 0.075] or retinopathy [1.27 (0.84–1.91), 0.261]. Increasing Z-score diastolic BP was significantly associated with nephropathy [1.81 (1.32 – 2.49), < 0.001] but not retinopathy [1.38 (0.92–2.05), 0.120] or neuropathy [0.86 (0.67–1.10), 0.230]. Our study shows varying strengths of associations of hypertension, systolic BP, and diastolic BP with microvascular dysfunction in different microcirculatory beds. Hypertension prevention and/or control may be valuable in the prevention/treatment of microvascular disease, especially nephropathy, and neuropathy.